2020
DOI: 10.1002/ajae.12036
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Food Waste as Household Production Inefficiency

Abstract: Measuring food waste at the individual household level has been nearly impossible because comprehensive, current data on uneaten food do not exist. By using food acquisition data, this article employs a new approach to estimating household‐level food waste via a stochastic production frontier model in which food waste is identified as input inefficiency. For households in our data, the average household wastes 31.9% of the food it buys, and this figure, using survey weights, translates to annual U.S. consumer‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 50 publications
5
76
0
Order By: Relevance
“…As well as the environmental significance, reducing fruit and vegetable waste may be particularly important for health (if it were to result in increased consumption) as meeting the 5 A DAY recommendation could help reduce risk of heart disease, stroke and some cancers (WHO/FAO ). Interestingly, analysis carried out using US data has indicated that those with a healthier diet actually generate more food waste than those with less healthy diets, likely due to the high perishability of fruit and vegetables (Yu & Jaenicke ). Higher income and food security was also associated with more food waste in this study.…”
Section: The Scale and Consequences Of Food Waste In The Ukmentioning
confidence: 99%
“…As well as the environmental significance, reducing fruit and vegetable waste may be particularly important for health (if it were to result in increased consumption) as meeting the 5 A DAY recommendation could help reduce risk of heart disease, stroke and some cancers (WHO/FAO ). Interestingly, analysis carried out using US data has indicated that those with a healthier diet actually generate more food waste than those with less healthy diets, likely due to the high perishability of fruit and vegetables (Yu & Jaenicke ). Higher income and food security was also associated with more food waste in this study.…”
Section: The Scale and Consequences Of Food Waste In The Ukmentioning
confidence: 99%
“…Yu and Jaenicke (2020) utilized food purchase and acquisition data from over 4,000 U.S. consumers from USDA National Household Food Acquisition and Purchase Survey (FoodAPS) to calculate caloric purchases and compared it to estimated caloric need based on individuals’ weights and energy expenditures, among other variables. They then estimated an efficiency frontier relating the minimum amount of food inputs needed to achieve a given energy expenditure.…”
Section: Defining and Measuring Household Food Wastementioning
confidence: 99%
“…Individuals off the frontier are inefficient in their food use, and greater inefficiency is argued to be tantamount to greater food waste. Yu and Jaenicke (2020) estimated that the average percentage of food wasted across all households was 31.9%. They found that their measures of food waste were positively correlated with income, food security, and healthier diets and was falling in household size and distance traveled to the retail outlet.…”
Section: Defining and Measuring Household Food Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Although suggesting that both our paper (Yu and Jaenicke 2020a) and Smith and Landry's paper (this issue) provide a novel methodological pathway for studying food waste, Brian Roe's comment elaborates on several important advantages (and disadvantages) of both empirical papers. Given the opportunity to reply, we would like to explore some of these topics even deeper.…”
mentioning
confidence: 97%